2018
DOI: 10.1101/403683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

General aspects of visceral leishmaniasis with or without HIV co-infection in Northeast Brazil

Abstract: 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The geographic overlap of HIV-1 and L. infantum infections raises the possibility of co-infection, which several groups have shown to increase morbidity and mortality (Coura-Vital et al, 2014;Lima et al, 2017Lima et al, , 2018Viana et al, 2017;Diniz et al, 2018;Fontoura et al, 2018;Luz et al, 2018;Rezaei et al, 2018;Sousa et al, 2018;Botana et al, 2019;Diro et al, 2019;Horrillo et al, 2019;Maia-Elkhoury et al, 2019;Prestes-Carneiro et al, 2019;Santos et al, 2019;Silva de Lima et al, 2019;van Griensven et al, 2019). Several groups have studied the extent of this overlap in several Brazilian regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geographic overlap of HIV-1 and L. infantum infections raises the possibility of co-infection, which several groups have shown to increase morbidity and mortality (Coura-Vital et al, 2014;Lima et al, 2017Lima et al, , 2018Viana et al, 2017;Diniz et al, 2018;Fontoura et al, 2018;Luz et al, 2018;Rezaei et al, 2018;Sousa et al, 2018;Botana et al, 2019;Diro et al, 2019;Horrillo et al, 2019;Maia-Elkhoury et al, 2019;Prestes-Carneiro et al, 2019;Santos et al, 2019;Silva de Lima et al, 2019;van Griensven et al, 2019). Several groups have studied the extent of this overlap in several Brazilian regions.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of studies worldwide (Oryan and Akbari, 2016;Grande et al, 2017;Zacarias et al, 2017;Bruhn et al, 2018;Guedes et al, 2018;Luz et al, 2018) and a recent systematic review (Fontoura et al, 2018) have demonstrated a high frequency of relapse of VL in PWH, as well as increased mortality. Relapse of VL has been reported after anti-leishmaniasis treatment, even years after the patient was considered clinically cured, especially in PWH and/or immunosuppressive conditions (Horrillo et al, 2019;Silva de Lima et al, 2019).…”
Section: Discussionmentioning
confidence: 99%